Analisa Informasi Citra MRI Cervical Potongan Sagital Pada Variasi Nilai Time Repetition (TR) Dengan Sekuens Short Tau Inversion Recovery (STIR) - Siti Masrochah; Fatimah Fatimah; Nurdianty Yunitaningrum (Poltekkes Kemenkes Semarang, 2020)
Background: STIR sequences used in the cervical spine due to the cervical spine is surrounded by lots of fluids and fat, to reinforce the picture of the cervical spine. According to Braun in 2003, TR on STIR used is 4000 ms. Meanwhile, according to Erika J. Ulbribh in 2011, TR on STIR sequences was used that 4860 ms. Based on the writer's observation in several hospitals with the same flight characteristics, the value of TR on STIR sequences different - different. At one hospital using TR 5000 ms, then at other hospitals using the TR 3000 ms. TR value is used based on the theory of 2000 ms.Methods: This research is a quantitative study with an experimental approach. Data were collected from May to June 2016 in the. The subjects of this study are volunteers by using a variation of the value of Time Repetition. It is caused during data capture none of the patients with the diagnosis of the lesion or tumour. image of five variations Repetition Time value is 4090 ms, 5190 ms, 6290 ms, 7390 ms and 8490 ms. Selection of variation based on the value of TR used.Results: From the statistical test result known that There are differences in image information MRI Cervical on the variation of the Time Repetition 4090 ms, TR 5190 ms, TR 6290 ms, TR 7390 ms, and TR 8490 ms to the value of ρ value of 0.000 (ρ 0, 05).That is because Repetition Time (TR) sequences Inversion Recovery (IR) should be long enough to provide opportunities so that Net Magnetization Vectors (NMV) can be in full recovery before the next 180 RF pulse inversion. If TR is too short then each network will be recovery with different levels which will ultimately affect the weighting (weighting) is generated.Conclusion: There are differences in Cervical MRI image information on the variation of the value of 4090 ms Repetition Time, TR 5190 ms, TR 6290 ms, TR 7390 ms, and TR 8490 ms to the value of ρ value of 0.000 (ρ 0.05).